How advertising relevance and consumer–Brand relationship strength limit disclosure effects of native ads on Twitter. Issue 1 (2nd January 2020) - Hayes, Jameson L.; Golan, Guy; Britt, Brian; Applequist, Janelle
Abstract: Present research builds upon native advertising research by examining the roles of advertising message relevance, consumer-brand relationship strength, and authorship. Two national experiments were conducted among active Twitter users ages 18–34. In Study 1 ( N  = 147), a 2 (disclosure: tweet/promoted tweet) X 2 (high-/low-ad message relevance) experiment showed that while disclosure had no effect on advertising outcomes, strong message relevance effects were present. Study 2 ( N  = 363), a 2 (weaker/stronger brand relationship strength) X 2 (disclosure: tweet/promoted tweet) X 3 (authorship: brand/influencer/peer) design, found that consumer–brand relationship strength also directly and positively influences attitude towards the brand, purchase intention and sharing intention; while significantly enhancing the positive message relevance impact on sharing intention, relevance's impact on purchase intention was lessened. Greater consumer–brand relationship strength influence on attitude towards the brand and purchase intention was present when native ads were authored by peers rather than brands or influencers.